Benzimidazole-derived Compounds Designed for Different Targets of Alzheimer’s Disease - Gulcan, Hayrettin O.; Mavideniz, Açelya; Sahin, Mustafa Fethi; Orhan, Ilkay Erdogan (Current Medicinal Chemistry, 2019)
Benzimidazole scaffold has been efficiently used for the design of various pharmacologically active molecules. Indeed, there are various benzimidazole drugs, available today, employed for the treatment of different diseases. Although there is no benzimidazole moiety containing a drug used in clinic today for the treatment of Alzheimer’s Disease (AD), there have been many benzimidazole derivative compounds designed and synthesized to act on some of the validated and non-validated targets of AD. This paper aims to review the literature to describe these benzimidazole containing molecules designed to target some of the biochemical cascades shown to be involved in the development of AD.
Keywords: glutaminyl cyclase